2014
DOI: 10.1093/humrep/deu101
|View full text |Cite
|
Sign up to set email alerts
|

Can healthy babies originate from oocytes with smooth endoplasmic reticulum aggregates? A systematic mini-review

Abstract: We have no conflicts of interest to declare and no funding was received.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 18 publications
0
41
0
Order By: Relevance
“…In 2013, the first births of healthy babies originating from SERa+ oocytes were published by Mateizel and colleagues [23]. A year later, a systematic mini-review of the literature, identified 171 apparently healthy babies from SERa+ cycles with 22 specifically from SERa+ oocytes [8]. Since then a recent publication [13] has added an extra ten healthy births from SERa+ oocytes and our centre 14 (submitted data).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In 2013, the first births of healthy babies originating from SERa+ oocytes were published by Mateizel and colleagues [23]. A year later, a systematic mini-review of the literature, identified 171 apparently healthy babies from SERa+ cycles with 22 specifically from SERa+ oocytes [8]. Since then a recent publication [13] has added an extra ten healthy births from SERa+ oocytes and our centre 14 (submitted data).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, centres that do transfer affected embryos do not always follow up obstetrical and neonatal data. One of the aims of this survey as well as the recent publication of a mini-review [8] is to inform centres on the importance of recording data and publishing the outcomes when affected oocytes are not discarded. Although the birth of healthy babies is encouraging, data is currently lacking to allow an eventual revision of the Alpha-ESHRE Consensus [24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations